Prognostic Factors of Severe Dengue Based on Individual Characteristics And Laboratory Examination: A Scoping Review - Manggar Sari, Arlyn; Susanti, Dwi; Fauzi, Muh; Dharmawan, Yudhy (Journal of Public Health for Tropical and Coastal Region, 2025)
Introduction: Dengue fever is a major health problem in 48 countries worldwide. Complications and death can occur in patients who experience shock or prolonged infection. Dengue severity can be predicted based on individual characteristics and laboratory test results. However, previous studies have reported different prognostic factors. This review aimed to identify the characteristics and laboratory findings associated with severe dengue.Methods: The inclusion criteria were observational studies published between January 2016 and May 2025 in the Scopus, PubMed, and Google Scholar databases, written in Indonesian or English, and available in full texts. Articles other than observational studies and those that did not provide PR/OR/RR were excluded from the study. Thirteen studies were eligible for assessment. This study followed the Preferred Reporting Items for Systematic Literature Reviews and Meta-Analyses (PRISMA) guidelines.Results: Patient characteristics that served as prognostic factors for severe dengue included male sex, abnormal nutritional status, age 15–49 years, presence of comorbidities, and receiving health care for more than 1–2 days of hospitalization. Laboratory findings that act as prognostic factors include hemoconcentration, thrombocytopenia, leukopenia, and low hemoglobin levels. Based on patient characteristics, the dominant prognostic factors were comorbidities, nutritional status, and duration of healthcare. According to the laboratory findings, the dominant factors were hemoconcentration and thrombocytopenia.Conclusion: The dominant prognostic factors for severe dengue are comorbidities such as hypertension, cardiovascular disease, and hemoconcentration. Further studies using a robust and comprehensive methodological approach are needed to validate the relationship between these prognostic factors.